Explaining China's Low Consumption : The Neglected Role of Household Income - Aziz, Jahangir (IMF Working Papers; Working Paper, 2007)
The Chinese government has recently focused on the need to increase consumption to rebalance the economy. A widely held view is that despite China's remarkably high growth, the share of consumption in total expenditure has been low and declining due to high and rising saving rate of Chinese households as uncertainty over provision of pensions, and healthcare and education costs have increased since the mid-1990s. This paper finds that the rise in saving rate has been a minor factor. Much larger has been the role of the declining share of household income in national income, which has occurred across-the-board in wages, investment income, and government transfers. The paper finds that financial sector weaknesses, by restricting firms' access to bank financing for working capital, have played quantitatively a major role in keeping wage and investment income shares low and on a declining trend.